A cross-national study on mental health, psychological distress and suicidal ideation among veterinarians in multiple European countries - Máté, Marietta; Várnai, Claire Helen; Ózsvári, László (Frontiers in Veterinary Science, 2025)
BackgroundThe suicide rate among veterinarians is alarmingly high, being twice that of other medical professionals and four times that of the general population. This study examined the occurrence of suicidal thoughts, tendencies, and mental health challenges among veterinarians in Hungary, Finland, Sweden, Germany, and from other Northern-European countries (Norway, Denmark and Estonia).MethodsAn online questionnaire of 55 items was developed and distributed between July 2021 and February 2022. A total of 724 veterinarians participated: 236 from Hungary, 218 from Finland, 157 from Sweden, 77 from Germany, 26 from Estonia, 5 each from Denmark and Norway. Factors such as country, age, gender, weekly working hours, job position and length of annual leave were assessed. Data were analyzed using Pearson’s chi-square test.ResultsThe results showed that work-related stressors significantly contributed to negative mental health across all surveyed countries. Among these stressors, clients’ expectations for prompt diagnosis were rated particularly high, with a mean of 4.34 ± 0.84 points on a Likert scale of 1 to 5, especially in Germany and Hungary, a difference considered statistically significant (ANOVA: p < 0.0001). Many veterinarians also reported high levels of anxiety related to their conscientiousness and punctuality at work, particularly in Hungary. In contrast, the emotional impact of performing euthanasia was ranked low, although this varied significantly by country (ANOVA: p < 0.0001). Younger respondents (aged 23–34 years) more often reported negative effects of their work on their mental health. Female veterinarians were more likely to seek professional counseling compared to men. Older veterinarians and those in leadership positions were more likely to manage their mental health effectively and seek help when needed, compared to younger veterinarians.ConclusionThese results highlight a worrying pattern of emotional distress in the veterinary field. Although the underlying causes of suicide are complex and multifactorial, addressing specific occupational stressors can play a critical role in improving mental health and reducing psychological risk in the profession. This study contributes to the growing research by providing cross-national data from underrepresented Central and Northern European countries, underscoring the importance of mental health strategies tailored to cultural and systemic contexts in the veterinary profession.